(untitled) (Journal of the Sociology and Theory of Religion, 2024)
The main objective of this article is to address the relationship between science and religion, from the perspective of a religious minority called the Baha’i faith, to understand and be able to expose the type of interaction between the two forms of knowledge. It must be considered that the Bahá’í faith is a young religion that emerged in the mid-19th century in Persia, within the framework of modernity. A religion that, little by little, has managed to consolidate itself as a universal religion, and for which science plays an important and significant role in the progress of civilization.